ASPECTS OF BALANCED NUTRITION OF VOLLEYBALL PLAYERS - Yuldashev Uzakbay Kengashovich (Web of Journals Publishing, 2024)
This article will cover the most important aspects of volleyball players' nutrition. Volleyball is a game that requires a lot of strength and energy. During the game, volleyball players often jump and make sharp accelerations. For the proper functioning of the body, a balanced diet is required, which helps athletes to be in good energy shape before important games and serious workouts.
Keywords: volleyball, nutrition, calories, proteins, fats, carbohydrates, exercise, nutrients.